Impact of Online Shopping on Consumer in FMCG sector - Lakshmi Sai Chandra Maddi, V V G Ravi Teja (International Journal of Advanced Science and Technology, 2020)
the fast-moving consumer good (FMCG) market is the Indian economy’s fourth-largest industry. As there is a rise in incomes, high-income consumers in urban areas are purchasing premium products instead of essential products. Consumers are liking to buy packaged goods that are of high quality and well packed. Today, people need everything quick, which brought distinction in products and that is the reason for the shrinking of some products. Here comes the importance of online shopping. It became very easier, faster and hassle-free to shop online on the web and mobile platforms. Since FMCG purchase is very time taking and less interesting shopping activity, online shopping became a remedy to overtake. The impact of online shopping on the consumer is very high due to this busy and competitive world. The impact of online shopping on the consumer is very high due to the busy and competitive market globally. This paper analyses the demographic characteristics of the users who like to buy FMCGs from online portals and the reasons which make them do so. This research shows the study on various dimensions influencing consumers in purchasing grocery through online shopping in a descriptive and quantitative research methodology. This research aims to draw a picture regarding the dimensions that influence consumers to shop online.